G384 Case report – nephronophthisis: The mutation is not the whole story. (27th April 2016) - Sabir, AH; Milford, DV; Nagy, A; Howie, A
Abstract : Aim: An unusual presentation of Juvenile Nephronophthisis with severe early cystic changes and rapid disease progression. Background: Nephronophthisis (NPH) – a frequent genetic cause of paediatric established renal failure (ERF) – is an autosomal recessive disorder causing chronic tubulointerstitial nephritis and cystic kidneys. It is classified by age of onset; Infantile, Juvenile or Adolescent and presents in isolation (85%) or as part of a syndrome e.g. Senior-Loken, Joubert, Jeune or Meckel-Gruber Syndrome. The infantile form (NPHP2 gene) is normally diagnosed within the first year, progressing to ERF by age 2 years. Methods: Our patient – a Caucasian girl – was diagnosed with NPH (NPHP1 gene mutation, homozygous deletion: 2q13, identified 6 months after presentation). She had no extra-renal manifestations of disease (normal MRI brain scan and no clinical features to suggest a syndromic diagnosis). Results: At presentation (age 4 years) she had very large cysts (Figure 1 ) which is unusual for the NPHP1 mutation. Her condition rapidly deteriorated with cystic expansion (Figures 2 and 3). She needed Peritoneal Dialysis 2 months after presentation and had a LRD (Live-Related Donor) renal transplant aged 5 years. Conclusion: There are at least 20 genes that cause NPH. NPHP1 mutations cause Juvenile NPH (jNPH) with mild symptom onset (polyuria, polydipsia) between 4–6 years of age. Initial cystic change is minimal but small medullary cysts appear later and progression to ERF occurs in the 2nd decade (mean age 13 years). The clinical progression of our patient was more in keeping with infantile NPH despite her mutation. Furthermore, her cystic changes are unusually large and more in keeping with those seen in Medullary-Cystic kidney disease (MCKD). Although NPH and MCKD were previously considered part of the same complex due to homogeneity of clinical and histological features, MCKD is distinct from NPH due to its AD inheritance, late onset of renal failure (post 4th decade), lack of extra-renal features and identification of the MCU1 gene. Despite having a mutation consistent with jNPH our patient had a clinical course more in keeping with infantile NPH and had cystic changes in keeping with MCDK.